Reading Durkheim con Galtung: Suicide and structural violence - Hincapié Zuleta, Ana María; Carmona Parra, Jaime Alberto (Revista Colombiana de Ciencias Sociales, 2026)
Introduction: This study aims to explore the relationship between suicide and structural violence, using a theoretical approach based on Johan Galtung’s theories on violence and the types of suicide of Émile Durkheim. Methodology: the study is situated within the interpretative paradigm, employing a qualitative, exploratory-level discourse analysis approach. Documentary analysis was used as the data collection technique. A total of 59 studies published in academic journals from different continents were reviewed. Results: Structural and cultural violence, deeply rooted in social and economic inequalities, following Galtung’s model, influence structural violence, which materializes in suicidal behaviors, especially among marginalized populations. Conclusion: it is necessary to continue with the line of research that depathologizes suicide and shifts interest from clinical and individual determinations to social interactions and structural violence, in order to build an authentic interdisciplinary perspective that contributes to the understanding of suicide as a multidetermined phenomenon.